Performing the jumbled city - Casagrande, Olivia (Manchester University Press, 2022)
Building on analyses of the relationship between race, aesthetics and politics, the volume elaborates on the epistemological possibilities arising from collaborative and decolonial methodologies at the intersection of ethnography, art, performance and the urban space. It moves from practice-based and collaborative research with young Mapuche and mestizo artists and activists in Santiago (Chile), drawing together a range of different materials: from artworks to theatre and performance; from graphics to audio and visual materials. An edited collection, the book is constructed by shifting between different authorships and changing perspectives from the individual to the collective. This approach, while to a certain extent within the classical structure of editors/authors, plays with the roles of researcher/research participant, highlighting the ambiguities, frictions and exchanges involved in this relationship. Elaborating on indigenous knowledge production, the book thus addresses the possibility of disrupting the social and material landscape of the (post)colonial city by articulating meanings through artistic and performative representations. As such, the essays contained in the book put forward alternative imaginations constructed through an aesthetic defined by the Mapuche concept of champurria ('mixed'): a particular way of knowing and engaging with reality, and ultimately an active process of home- and self-making beyond the spatialities usually assigned to colonised bodies and subjects. Actively engaging with current debates through collective writing by indigenous people raising questions in terms of decolonisation, the book stands as both an academic and a political project, interrogating the relationship between activism and academia, and issues of representation, authorship and knowledge production.